A systematic review of pharmacist-led audit and feedback interventions to influence prescribing behaviour in general practice settings. (26th March 2021) - Carter, M; Abutheraa, N; Ivers, N; Grimshaw, J; Chapman, S; Rogers, P; Simeoni, M; Watson, M
Abstract: Introduction: Audit and Feedback (A&F) involves measuring data about practice, comparing it with clinical guidelines, professional standards or peer performance, and then feeding back the data to individuals/groups of health professionals to encourage change in practice (if required). A 2012 Cochrane review (1) found A&F was effective in changing health professionals' behaviour and suggested that the person who delivers the A&F intervention influences its effect. Increasingly, pharmacists work in general practice and often have responsibility for medication review and repeat prescriptions. The effectiveness of pharmacist-led A&F in influencing prescribing behaviour is uncertain. Aim: This secondary analysis from an ongoing update of the original Cochrane review aims to identify and describe pharmacist-led A&F interventions and evaluate their impact on prescribing behaviour in general practice compared with no intervention. Methods: This sub-review is registered with PROSPERO: CRD42020194355 and complies with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines (2) . For the updated Cochrane review, the Cochrane Effective Practice and Organization of Care Group searched MEDLINE (1946 to present), EMBASE, CINAHL and Cochrane Library (March 2019) to identify randomised trials featuring A&F interventions. For this sub-review, authors screened titles and abstracts (May 2020) to identify trials involving pharmacist-led A&F interventions in primary care, extracted data, and assessed risk of bias (RoB) in eligible studies. Review results are summarised descriptively. Heterogeneity will be assessed and a random-effects meta-analysis is planned. Publication bias for selected outcomes and the certainty of the body of evidence will be evaluated and presented. Sub-group analyses will be conducted. Results: Titles and abstracts of 295 studies identified for inclusion in the Cochrane A&F review update were screened. Eleven studies (all cluster-randomised trials) conducted in 9 countries (Denmark, Italy, Netherlands, Norway, Republic of Ireland, UK, Australia, Malaysia, USA) were identified for inclusion (Figure 1). Six studies had low RoB, two had high risk due to dissimilarities between trial arms at baseline and/or insufficient detail about randomisation, and three studies had unclear RoB. Studies examined the effect of A&F on prescribing for specific conditions (e.g. hypertension), medications (e.g. antibiotics), populations (e.g. patients >70), and prescribing errors (e.g. inappropriate dose). The pharmacist delivering A&F was a colleague of intervention participants in five studies. Pharmacists' levels of skill and experience varied; seven studies reported details of pharmacist training undertaken for trial purposes. A&F interventions in nine studies demonstrated changes in prescribing, including reductions in errors or inappropriate prescribing according to the study aims and smaller increases in unwanted prescribing compared with the control group. Data analyses are ongoing (results will be available for the conference). Conclusion: The preliminary results demonstrate the effectiveness of pharmacist-led A&F interventions in different countries and health systems with influencing prescribing practice to align more closely with guidance. Studies measured different prescribing behaviours; meta-analysis is unlikely to include all 11 studies. Further detailed analysis including feedback format/content/frequency and pharmacist skill level/experience, work-base (external/internal to recipients), will examine the impact of specific features on intervention effectiveness. References: 1. Ivers N, Jamtvedt G, Flottorp S, Young JM, Odgaard-Jensen J, French SD, et al. Audit and feedback: effects on professional practice and healthcare outcomes. Cochrane Database Syst Rev. 2012(6):CD000259. 2. Moher D, Liberati A, Tetzlaff J, Altman DG, Group P. Preferred reporting items for systematic reviews and meta-analyses: the PRISMA statement. PLoS Med. 2009;6(7):e1000097.